2020
DOI: 10.3174/ajnr.a6478
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Disease and Outcomes of Mechanical Thrombectomy for Acute Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE: The increased severity of white matter disease is associated with worse outcomes and an increased rate of intracerebral hemorrhage in patients with ischemic stroke undergoing thrombolytic treatment. However, whether white matter disease is associated with outcomes in patients undergoing endovascular treatment remains unclear. MATERIALS AND METHODS: In this prespecified exploratory analysis of our prospective multi-institutional study that enrolled consecutive adult patients with anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 31 publications
6
40
1
Order By: Relevance
“…Among them, Seventy-five articles were repetitive with the remaining 147 articles being screened by the title, abstract, and full text. Finally, 7 original studies [22][23][24][25][26][27][28] were included, which included a prospective cohort study [28] and six retrospective cohort studies [22][23][24][25][26][27].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Seventy-five articles were repetitive with the remaining 147 articles being screened by the title, abstract, and full text. Finally, 7 original studies [22][23][24][25][26][27][28] were included, which included a prospective cohort study [28] and six retrospective cohort studies [22][23][24][25][26][27].…”
Section: Search Resultsmentioning
confidence: 99%
“…Two and five studies were performed in China [24,25] and The United States, respectively [22,23,[26][27][28]. In addition, two studies [22,25] used the Fazekas Scale to classify LA severity while five studies [23,24,[26][27][28] used the van Swieten Scale. We used the Newcastle-Ottawa Scale to assess the risk of bias in cohort studies, including selection, comparability, and outcome biases, which indicated a low risk of bias.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…These reports are consistent with our findings. Since the odds of major NCD increases with every ml lesion volume, a small stroke lesion contributes to favorable clinical outcome after endovascular stroke therapy [ 43 ], especially when the WMH burden is low [ 44 ]. Thus, reducing the stroke lesion volume is important for reducing the odds of major NCD.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 5,277 records assessed with titles and abstracts, the full texts of 231 articles were reviewed. Overall, 20 articles published between 2012 and 2020 met our inclusion criteria and were finally included in this meta-analysis (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The study characteristics are summarized in Table 1.…”
Section: Study Characteristics and Qualitative Assessmentmentioning
confidence: 99%